Micro hydro Generator - Teh, Choon Yan (Universiti Teknologi Petronas, 2011)
There is a high demand of water usage in Malaysia due to the high population. There is 16,283 million litres of water is used every day. This large amount of water can be fully utilized to produce electricity. Besides that, electricity demand for the residential sector also experience strong growth of 4.9 percent per year due to improving living standards. When the user turns on the tap, there is water flow inside the domestic pipeline and hence produce kinetic energy. Therefore, the aim of this project is to generate electricity through pipeline in the household using micro hydro generator. The flow of water is able to turn the turbine. The turbine is attached to the generator whereby electricity will be generated. Besides that, the choosing of turbine and generator are very important in determining the performance of the project. Hence, feasibility study of Malaysia water system is conducted to obtain the data such as flow rate, water consumption and pressure head. The data obtained will be used to determine how much energy is actually converted and at the same time determine the size of generator needed. Several experimental testing is conducted which are electric circuit testing, open circuit test, turbine test and system test. A prototype of the micro hydro generator is been developed and it is able to generate electricity using the flow of water in domestic pipeline.